Gene action studies in sunflower (Helianthus annuus L.): Gene action studies in sunflower (Helianthus annuus L.) - M K GHODKE; J V SHINDE; M Y DUDHE; H P MEENA (Journal of Oilseeds Research, 2023)
The present investigation was conducted to study the gene action in sunflower. Thirty-two hybrids developed by using Four CMS and eight restorer lines in L x T design. The hybrids and parents were evaluated in RBD at ORS, Latur during Rabi-2021-22 for ten quantitative traits. Analysis of variance for means revealed significant differences for all the ten characters studied. CMS-249A was found to be good general combiner for head diameter, 100-seed weight, volume weight, hull content, oil content and seed yield/plant. Among the testers R/HA-1 was found good general combiner for days to 50 % flowering, days to maturity, plant height, head diameter, seed filling (%), 100-seed weight, volume weight (g/100ml), hull content and seed yield/plant. For oil content IR-1-1 exhibited high gca effect. Out of 32 hybrids the hybrids CMS-47A x EC-279309-1 was with good sca effect for seed yield and component traits. The variance due to SCA was greater than that of GCA for all the characters except days to maturity and plant height. Which indicated that the non-additive gene action played important role for the inheritance of these traits whereas days to maturity and plant height were governed by additive gene action.